Kennedy greeting parents of new students, 1967 (1967)
[00:00:00] Robert Kennedy greets audience [00:00:08] He explains the itinerary for the parents' day of viewing the campus [00:00:51] He says that this is the first time Cal Poly has ever invited parents [00:01:03] He is surprised by the amount of parents since his kids would not have told him [00:01:35] Kennedy says he will pinpoint three things: Week of Welcome, Higher Education, and Higher Education regarding Cal Poly [00:02:03] He begins explaining WOW and the students' role in it [00:02:59] There are also special programs that are tailored for specific aspects a student might be interested in [00:03:11] There are two speakers that are for both freshman and transfer students [00:03:32] WOW clubs will meet with the students' counselors, faculty advisors, academic departments while also registering and touring the campus [00:04:16] There will also be social events for the WOW Clubs like: dances, recreational events, watermelon feed, beach party, as well as climbing the "P" [00:04:33] WOW concludes with a Church night, the night before classes [00:04:57] Kennedy explains the importance of WOW week for students at Cal Poly [00:05:25] He then explains the system of Higher Education in California [00:06:07] He states the differences between Junior, State, Private, and Universities of California colleges [00:07:08] The agency that pulls these colleges together in California is the Coordinating Council [00:07:58] He then explains who governs each type of college in California [00:08:45] Following, he explains the admissions and entrance standards [00:09:20] The state colleges are comprised of the fastest growing college system of higher administration in the western world [00:10:19] He explains how state colleges provide in depth training for careers [00:10:51] He begins explaining Cal Poly's place in Higher Education [00:11:02] He also highlights the history of Cal Poly [00:11:30] He states that Cal Poly stopped allowing women to attend for 27 years [00:11:43] In 1940, Cal Poly was authorized to grant the Bachelor of Science for the four year curriculum [00:11:51] The first class to receive a BS degree was in 1942 [00:12:20] After a few historical events, the teaching staff has grown and the facilities have been renovated to keep up with enrollment growth [00:12:45] He then explains the imperative differences of Cal Poly and other State universities [00:12:50] Cal Poly focuses on the applied fields of agriculture, engineering, business, and home economics [00:13:17] It also was one of the first state colleges to have any departments of engineering, and it is one of the largest undergraduate enrollments in the West [00:13:51] Cal Poly's faculty members are some of the best educators that are involved in research, industry, and more [00:14:35] He explains how each students' curriculum is focused on its major while also incorporating support and general education courses [00:14:47] Cal Poly's curriculum is referred to as the "Upside Down" program [00:15:46] Past students, employers, and parents refer to Cal Poly as a "Healthy, friendly, constructive environment" [00:16:18] There are also other Cal Poly groups that heighten the positive experience at the college [00:16:43] Cal Poly received a framed copy of a joint resolution from the legislature, commending Cal Poly [00:17:53] Kennedy wants to provide the best educational experience possible for Cal Poly's students [00:18:35] Most students complain about the food in the cafeteria [00:19:25] Cal Poly students are expected to play an active role in decision making [00:20:16] Kennedy would now like to introduce the represented faculty members [00:20:47] The faculty members that are present, volunteered for this assignment [00:21:21] He then introduces each faculty member and the college they represent [00:23:56] Kennedy interrupts himself by telling an anecdote about one of the faculty members [00:25:04] He then resumes with the faculty introductions [00:25:54] Kennedy asks about the time schedule for refreshments [00:26:03] He asks if anyone has anyone questions [00:26:50] Dr. Lawson reminds the audience that there are special tours [00:28:00] Kennedy says everyone can now gather to the patio and enjoy the refreshments [00:28:40] Classical music begins playing